The impact of bio-label on the decision-making behavior - Šola, Hedda Martina; Gajdoš Kljusurić, Jasenka; Rončević, Ivana (Frontiers in Sustainable Food Systems, 2022)
Unlike traditional research methods used for investigating consumer responses to different stimuli such as surveys, interviews or focus groups, recently, the autonomic neuropsychological measures have been implemented within the neuromarketing field to obtain subconscious preferences from the consumer’s brain. In the current study, the webcam-based eye-tracking technology is used to analyze both visual and emotional reflects of the consumer green purchasing behavior, which has grown notably in the last decade. The main interest was to assess whether the color packaging affects the BIO label and if such a label is essential for consumers’ purchasing behavior. The packaging designs of the two-well known products from one of Croatia’s most prominent food processing companies were manipulated in packaging color and the BIO label placement. The results have shown that regardless of the package design and the placement of the BIO label, participants elicited higher intensities of negative emotion. The eye-tracking metrics showed that for both products the color of the packaging and the BIO label placement matter.